The Impact of Brand Equity on Gen-Y in the Purchase of Foreign Cosmetic Products - Feng, Pan Pan (2014)
The research aims to investigate the impact of brand equity on generation Y in the purchase of foreign cosmetic products in Malaysia. For this purpose, four elements as brand equity’s components were identified that has potential affect purchasing foreign cosmetic products, and they are Brand Loyalty, Brand Awareness, Brand Association, and Perceived Quality. The paper clarifies the interrelation between the four brand equity model components and purchase decision. A quantitative approach was adopted, with the questionnaire as the main tool. SPSS software was used for a descriptive analysis, and PLS estimation software was used to test the relationship between the various constructs. Based on a sample of 301 Gen-Y consumers, structural equation modeling is used to test hypotheses. The research reveals that brand awareness, brand loyalty and perceived quality have a significant impact on Gen-Y in purchase of foreign brands cosmetic products. The paper suggests that local cosmetic marketers should carefully consider the brand equity components when designing their branding strategies. The local cosmetic marketers should also enhance brand awareness to affect consumer purchase behavior in order to strengthen their competitive position in relation to foreign brands. A total five chapters are included in this research, namely, introduction, literature review, research methodology, findings and discussion, conclusion and recommendations.